The impact of management and strategic controls on firm performance: an empirical study on the UK. (1st January 2014) - Basuony, Mohamed A.K.
This study focuses on and gauges the dimensions of both management and strategic control. It also defines the variables that affect the management accounting practices which will consequently affect the firm performance through management and strategic control. This study uses cross-sectional data that is derived from the FAME database in UK. Regression analysis is used to explain the relationship and the effect of management and strategic controls, industry type and firm size on firm performance. The results of this study indicate that management control and industry type have an effect on return on assets and profit margin while strategic control has an effect on competitive position as a measure of firm performance. Furthermore, this study proved that there is a significant difference in using management and strategic controls between large firms and SMEs while there is no difference between product-based and service firms in using management and strategic controls.